Sosialisasi dan Pendampingan Pelaksanaan Good Manufacturing Practices (GMP) di UD Annisa, Wonosobo - Aini, Nur; Dwiyanti, Hidayah; Setyawati, Retno; Sustriawan, Budi; Alfiyah, Silma Darojatun (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
This activity aims to find out the influence of socialization and assistance to the level of implementation of Good Manufacturing Practices (GMP) at UD Annisa, Wonosobo. Activities are conducted by the method of action research through the initial evaluation of activities, preparation of quality documents, socialization and assistance and final evaluation activities.